Financial Sector Assessment : Morocco - World Bank (World Bank, Washington, DC, 2017)
A joint International Monetary Fund (IMF)-World Bank mission visited Rabat and Casablanca in 2015, to assess the soundness and resilience of the banking system, the state of play in financial inclusion and infrastructure, the oversight frameworks for banking, capital markets and financial market infrastructures, crisis preparedness, and update the findings of the Financial Sector Assessment Program (FSAP) conducted in 2007. This report summarizes the main findings of the mission, identifies key financial sector vulnerabilities, and provides policy recommendations. This report should be read in conjunction with the Financial Sector Stability Assessment of the IMF available at https://www.imf.org/external/country/mar/index.htm.